Clomiphene citrate versus letrozole for ovulation induction in anovulatory infertility: a prospective study - Soni, Monica; Kalal, Gajendra Kumar; Meena, Arti; Sharma, Anita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of this study was to compare clomiphene citrate with letrozole for ovulation induction in anovulatory infertile women. Methods: This study was conducted in the infertility clinic and department of obstetrics and gynecology, S.P. Medical College and Associated P. B. M. Hospital, Bikaner, Rajasthan, from 1st August 2018 to 31st July 2019. The study group comprised of infertile females attending infertility clinic or gynae outdoor in department of obstetrics and gynecology, S. P. Medical College Bikaner for infertility. 100 women with anovulatory infertility were enrolled in the study after fulfilling the inclusion and exclusion criteria. Proper counseling was done and written informed consent taken. Results: Ovulation rate was statistically significantly greater in letrozole group. Monofollicular development was statistically significant greater in let group (CC 18%, Let 66%). The endometrial thickness on the day of ßhCG administration in CC group was 7.40±1.08 mm and in let group was 8.20±0.82 mm. Letrozole treated cases had better trilaminar pattern of endometrium as compared to clomiphene. The pregnancy rate was higher in letrozole group. Conclusions: As compare to clomiphene, letrozole is associated with higher pregnancy rate and ovulation rates among infertile women with anovulation.